The effect of higher protein dosing in critically ill patients with high nutritional risk (EFFORT Protein): an international, multicentre, pragmatic, registry-based randomised trial. Issue 10376 (18th February 2023) - Heyland, Daren K; Patel, Jayshil; Compher, Charlene; Rice, Todd W; Bear, Danielle E; Lee, Zheng-Yii; González, Victoria C; O'Reilly, Kevin; Regala, Racquel; Wedemire, Courtney; Ibarra-Estrada, Miguel; Stoppe, Christian; et al.
Summary: Background: On the basis of low-quality evidence, international critical care nutrition guidelines recommend a wide range of protein doses. The effect of delivering high-dose protein during critical illness is unknown. We aimed to test the hypothesis that a higher dose of protein provided to critically ill patients would improve their clinical outcomes. Methods: This international, investigator-initiated, pragmatic, registry-based, single-blinded, randomised trial was undertaken in 85 intensive care units (ICUs) across 16 countries. We enrolled nutritionally high-risk adults (≥18 years) undergoing mechanical ventilation to compare prescribing high-dose protein (≥2·2 g/kg per day) with usual dose protein (≤1·2 g/kg per day) started within 96 h of ICU admission and continued for up to 28 days or death or transition to oral feeding. Participants were randomly allocated (1:1) to high-dose protein or usual dose protein, stratified by site. As site personnel were involved in both prescribing and delivering protein dose, it was not possible to blind clinicians, but patients were not made aware of the treatment assignment. The primary efficacy outcome was time-to-discharge-alive from hospital up to 60 days after ICU admission and the secondary outcome was 60-day morality. Patients were analysed in the group to which they were randomly assigned regardless of study compliance, although patients who dropped out of the study before receiving the study intervention were excluded. This study is registered with ClinicalTrials.gov, NCT03160547 . Findings: Between Jan 17, 2018, and Dec 3, 2021, 1329 patients were randomised and 1301 (97·9%) were included in the analysis (645 in the high-dose protein group and 656 in usual dose group). By 60 days after randomisation, the cumulative incidence of alive hospital discharge was 46·1% (95 CI 42·0%–50·1%) in the high-dose compared with 50·2% (46·0%–54·3%) in the usual dose protein group (hazard ratio 0·91, 95% CI 0·77—1·07; p=0·27). The 60-day mortality rate was 34·6% (222 of 642) in the high dose protein group compared with 32·1% (208 of 648) in the usual dose protein group (relative risk 1·08, 95% CI 0·92–1·26). There appeared to be a subgroup effect with higher protein provision being particularly harmful in patients with acute kidney injury and higher organ failure scores at baseline. Interpretation: Delivery of higher doses of protein to mechanically ventilated critically ill patients did not improve the time-to-discharge-alive from hospital and might have worsened outcomes for patients with acute kidney injury and high organ failure scores. Funding: None.